STUDY ON THE NECESSITY OF PRACTICING PHYSICAL EXERCISES IN HIGH SCHOOL STUDENTS FROM BAC?U, ROMÂNIA (Fiep Bulletin - online, 2020)
The observations made in the last decades demonstrate a certain tendency to decrease the parameters of the physical and functional capacities of the body of all generations of Romanian citizens.Among the major causes of this phenomenon is the reduction of the motor activities of the contemporary man (hypodynamics), as well as the increase of the psychic efforts.In this sense, the prophylaxis actions that directly involve attracting and promoting physical activities in leisure activities are indispensable.From studying the existing bibliographic materials we realized that information regarding the possibilities of practicing the free time activities and especially the weight of these in the time budget of the high school students are non-existent.For this reason, we considered that conducting an investigation that would bring more information in this direction may be a benchmark for larger investigations that will influence the possibility of practicing physical exercises in high school students in Bac?u.
Keywords: study; physical exercises; high school